2021 IEEE International Symposium on Mixed and Augmented Reality (ISMAR) 2021
DOI: 10.1109/ismar52148.2021.00014
|View full text |Cite
|
Sign up to set email alerts
|

Perception-Driven Hybrid Foveated Depth of Field Rendering for Head-Mounted Displays

Abstract: In this paper, we present a novel perception-driven hybrid rendering method leveraging the limitation of the human visual system (HVS). Features accounted in our model include: foveation from the visual acuity eccentricity (VAE), depth of field (DOF) from vergence & accommodation, and longitudinal chromatic aberration (LCA) from color vision. To allocate computational workload efficiently, first we apply a gaze-contingent geometry simplification. Then we convert the coordinates from screen space to polar space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Foveated rendering has been shown to potentially mitigate cybersickness [23,24]. While various foveated rendering algorithms are available, we have opted to utilize a conventional depth-of-field rendering implementation because of its accessibility and its ability to be easily parameterized.…”
Section: Depth-of-field Renderingmentioning
confidence: 99%
“…Foveated rendering has been shown to potentially mitigate cybersickness [23,24]. While various foveated rendering algorithms are available, we have opted to utilize a conventional depth-of-field rendering implementation because of its accessibility and its ability to be easily parameterized.…”
Section: Depth-of-field Renderingmentioning
confidence: 99%
“…Results of the perceptual study showed that tracing rays reduced by more than 69% while rendering quality of this system was rated almost on par with full rendering. Liu et al [149] developed a mathematical model to simulate the DoF effects of human eyes in VR and subsequently performed DoF-based stochastic sampling to simulate retinal blur according to this mathematical model.…”
Section: Multi-spatial Resolution Based Ray Tracingmentioning
confidence: 99%